2022
DOI: 10.1038/s41598-022-05344-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis spores as delivery system for nasal Plasmodium falciparum circumsporozoite surface protein immunization in a murine model

Abstract: Malaria remains a widespread public health problem in tropical and subtropical regions around the world, and there is still no vaccine available for full protection. In recent years, it has been observed that spores of Bacillus subtillis can act as a vaccine carrier and adjuvant, promoting an elevated humoral response after co-administration with antigens either coupled or integrated to their surface. In our study, B. subtillis spores from the KO7 strain were used to couple the recombinant CSP protein of P. fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The spores were characterized as possessing the possibility of increasing immunogenicity of the Pfcsp, hence inducing high levels of IgG. 28 These proofs of concept results provide novel facts to be applied in the design of effective adjuvants of ongoing vaccines.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The spores were characterized as possessing the possibility of increasing immunogenicity of the Pfcsp, hence inducing high levels of IgG. 28 These proofs of concept results provide novel facts to be applied in the design of effective adjuvants of ongoing vaccines.…”
Section: Introductionmentioning
confidence: 95%
“…27 The molecular structure of the vaccine antigen is made up of 19 NANP central tandem repeats and the N-terminus of the amino acids in the hepatitis B surface antigen attached to the C-terminus of the CSP. 28 The RTS, S/As01 vaccine is made of a combination of the RTS, S antigen coupled with the AS01 adjuvant, 29 and the RTS, S/AS02 vaccine is made of a combination of the RTS, S antigen coupled with the adjuvant composed of monophosphoryl lipid A and Quillaja Saponaria Molina in an oil-in-water emulsion. 4 RTS, S vaccine targets CSP of the Pf trying to block its development, 30 during the pre-erythrocytic stage before the parasite invades the liver cells.…”
Section: The P Falciparum -Life Cycle and Vaccine Targetsmentioning
confidence: 99%
“…The release of genetically modified microorganisms into nature and their clearance can sometimes be a drawback. To overcome this issue, a non-recombinant to display antigens on the spore surface was proposed by Huang and collaborators in 2010 [104], and various model antigens have been efficiently displayed [106][107][108][109]. This approach uses spores' negatively charged and hydrophobic surface layer to adsorb foreign proteins and is more efficient at acidic pH [110][111][112].…”
Section: Multi Antigens Spore-based Mucosal Vaccinementioning
confidence: 99%
“…Antigen-adsorbed spores have been used to immunize mice mucosally, and protective humoral and cellular immune responses have been measured [109,110]. For example, a report by Isticato et al has shown that LTB of E. coli was present on the spore surface in its pentameric native form when adsorbed on the spore surface, improving the antigen recognition by its natural receptor and activation of a proper immune response [106].…”
Section: Multi Antigens Spore-based Mucosal Vaccinementioning
confidence: 99%
“…In addition, it induces immune responses such as an increase in IgG and IgA levels, regulation of the balance between Th1 and Th2 pathways, induction of interferon‐gamma (IFN‐γ) and Th1 cytokines, as well as the pro‐inflammatory tumour necrosis factor beta cytokine. It is also used in vaccine formulation as an adjuvant (Amuguni & Tzipori, 2012 ; de Almeida et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%